The Concept of Memayu Hayuning Bawana Perspective of Marcus Aurelius: A Descriptive Analysis Study - Nur Muhammad Khoirul Umam; Muhlas (al-Afkar, Journal For Islamic Studies, 2023)
It has become an unavoidable thing that modernization also brings negative effects. As a result, westernized behavior, moral decadence and spiritual dryness appear to be increasingly widespread. This needs a way as an antidote to this. One way is to return to the principles of life that are used as a form of local wisdom. The principle of life is Memayu Hayuning Bawana. This Javanese philosophy has a deep meaning that directs humans to their main goal, namely obtaining true happiness. In this study, the philosophical concept of Memayu Hayuning Bawana will be studied through the perspective of a Stoicist figure, Marcus Aurelius. This research is a type of qualitative research with descriptive analysis. There are two types of research data sources, namely primary and secondary. The data collection method is literature research which can be interpreted as an activity to search for relevant themes using several materials such as books, theses, dissertations, articles and so on. After that, the data was analyzed using the model from Miles and Huberman namely reduction, data display, and conclusion. The results of this study indicate that the concept of meayu hayuning bawana is an attempt by the Javanese to protect, care for and beautify life. These efforts can be centered on three values, namely the relationship between humans and nature, God and humans. When the three values ​​are aligned, the peak that will be achieved is a life that is safe and happy in essence.